Faktor Yang Mempengaruhi Kepatuhan Penulisan Resep Sesuai Formularium - Siti Mahfudhoh; Thinni Nurul Rohmah (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2015)
ABSTRACT Based on data from January - April 2014 found that obedience of prescription writing based on formularium in Outpatient Installation of Islam Jemursari Hospital only amounted to 87.9%. The purpose of this study was to analyze the factors that affect the obedience of prescription writing based on formularium. This study was an observational analitic cross sectional study. Data analysis using Spearman correlation test (α = 0.05). Obedience of prescription writing based on formularium mostly in the category of obedience (37.8%). Spearman correlation test showed no correlation between the status of the location (p = 0.166), the legitimacy of authority figures (p = 0.841), and the status of an authority figure (p=0,549) with the obedience of prescription writing based on formularium (p = 0.166). There was a significant relationship between personal responsibility (p = 0.005), peer support (p = 0.007), and the proximity of authority figures (p = 0.002) with obedience of prescription writing based on formularium. The conclusion that can be drawn is appropriate prescribing formulary can be improved by providing incentives and sanctions of the pieces and there are electronic formulary list. Keywords: formulary, obedience, prescription